Implementing mathematical morphology in ISETL-LINDA - Rowstron, A.I.T; Wood, A.M (Fifth International Conference on Image Processing and its Applications, 1995)
Presents the description of a parallel implementation of mathematical morphology using the LINDA model of parallel communication embedded within ISETL. The morphological operation of dilation of binary images is considered in detail, with an ISETL implementation given initially, then a description of how this was converted to run in a parallel version of ISETL, ISETL-Linda.